Brain drain in Turkey: Push and pull effects - Çoban, Elif (My University, 2019)
Migration among countries, which stems from economic, social and political and individual-specific differences, has also brought some questions about the interpretation of these movements. Especially, migration in emerging economies has been the subject for many studies with different approaches over time. This study is mainly elaborated on international movements of skilled labor in Turkey. Highly skilled migrants in the context of the international movement of labor are also treated as consumers or investors of human capital in addition to suppliers of labor. In this study movements of the skilled human capital, which takes a role as a factor of production in understanding the different levels of prosperity and income among countries in the new growth theories, has been discussed with the scope of the “brain drain”. As an integral part of international migration, the brain drain originated from the developing countries leads to deterioration in the source economy while highskilled immigrants improve productivity and innovation in the destination country. Current data including competitiveness, attractiveness and fragility indexes of brain drain in Turkey have been analyzed in order to compare the countries attracting brain drain and identify the factors affecting the decision-making process of choosing host countries. A sample of 148 Turkish citizens with tertiary education residing abroad is chosen to conduct a survey about the underlying motives for leaving the origin country and choosing the destination country. By comparing 27 countries in which participants reside with reference to the source country, the leading motives affecting the decision of highly skilled migrants have been investigated. After the detailed descriptive analysis of the cross-sectional survey data, the push and pull factors in the light of “stay” or “go” decision are discussed.

Ekonomik, sosyal ve politik ve bireye özgü farklılıklardan kaynaklanan ülkeler arasındaki göç, bu hareketlerin yorumlanması hakkında bazı soruları da beraberinde getirmiştir. Özellikle, gelişmekte olan ekonomilerdeki göç zaman içinde farklı yaklaşımlarla yapılan birçok araştırmaya konu olmuştur. Bu çalışma, ağırlıklı olarak, Türkiye'deki vasıflı emeğin uluslararası hareketlerine odaklanmaktadır. Emeğin uluslararası hareketi bağlamında değerlendirilen yüksek vasıflı göçmenler, emek tedarikçisi olmalarının yanı sıra beşeri sermaye yatırımcısı veya tüketici olarak da değerlendirilmektedir. Bu çalışmada, yeni büyüme literatüründe ülkeler arasında farklı refah ve gelir seviyelerinin anlaşılmasında üretim faktörü olarak rol oynayan yetenekli insan sermayesinin hareketleri “beyin göçü” kapsamında tartışılmıştır. Uluslararası göçün ayrılmaz bir parçası olarak, gelişmekte olan ülkelerden kaynaklanan beyin göçü kaynak ekonomisinde bozulmaya yol açarken, yüksek vasıflı göçmenler hedef ülkede üretkenliği ve inovasyonu artırmaktadır. Türkiye'deki beyin göçünün rekabetçiliği, çekiciliğini ve kırılganlık indekslerini içeren güncel veriler, beyin göçünü çeken ülkeleri karşılaştırmak ve ev sahibi ülke seçiminde karar alma sürecini etkileyen faktörleri belirlemek amacıyla analiz edilmiştir. Yurt dışında ikamet eden yükseköğrenime sahip 148 Türk vatandaşının menşe ülkesinden ayrılmasının ve varış ülkesini seçmesinin temel nedenleri ile ilgili bir anket yapmak için seçilmiştir. Katılımcıların bulundukları 27 ülkeyi kaynak ülke referansı ile karşılaştırarak, yüksek vasıflı göçmenlerin kararını etkileyen ana nedenler araştırılmıştır. Yatay kesit anket verilerinin detaylı tanımlayıcı analizinden sonra, “Kalmak” ve “Gitmek” kararını etkileyen itici çekici faktörler tartışılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: International labor migration; Human capital; Skilled migration; Brain drain; Uluslararası emek göçü; Beşeri sermaye; Vasıflı göç; Beyin göçü